The Formation of Protein–Chitosan Complexes: Their Interaction, Applications, and Challenges - Yufeng Xie; Jiaqi Ding; Yue Li; Pengfei Wei; Shiying Liu; Rui Yang (Foods)
Protein–polysaccharide interactions have been a subject of considerable interest in the field of food science. Chitosan is the most prominent and naturally occurring polysaccharide with a positive charge, and its hydroxyl and amino groups facilitate protein–chitosan interactions due to their diverse biochemical activities. The complexation of chitosan enables the modification of proteins, thereby enhancing their value for applications in the food and nutrition industry. This paper presents a summary of the complexes formed by chitosan and different proteins, such as lactoglobulin, egg white protein, soybean isolate protein, whey isolate protein, and myofibrillar protein, and systematically describes the modes of interaction between proteins and chitosan. The effects of protein–chitosan interactions on functional properties such as solubility, emulsification, antioxidant activity, and stability are outlined, and the potential applications of protein–chitosan complexes are discussed. In addition, the current challenges associated with the formation of protein–chitosan complexes and potential solutions to these challenges are highlighted. This paper provides an overview of the current research progress on the interaction of proteins with chitosan and its derivatives in the food industry.